2022
DOI: 10.1080/02813432.2022.2142796
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and management strategies of Norwegian GPs during the COVID-19 pandemic: a longitudinal interview study

Abstract: Objective When the COVID-19 pandemic reached Norway, primary health care had to reorganize to ensure safe patient treatment and maintain infection control. General practitioners (GPs) are key health care providers in the municipalities. Our aim was to explore the experiences and management strategies of Norwegian GPs during the COVID-19 pandemic - over time, and in the context of a sudden organizational change. Design Longitudinal qualitative interview study with two in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…GPs shaped their task boundaries [ 17 ], and the room for manoeuvre they had meant that they performed work tasks they normally did not do. Consistent with previous studies carried out during the COVID-19 pandemic [ 7 , 11 ], GPs proved their ability to improvise and use creative strategies. GPs in our study felt that they managed problems as they arose and tried to fight the pandemic to the best of their ability.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…GPs shaped their task boundaries [ 17 ], and the room for manoeuvre they had meant that they performed work tasks they normally did not do. Consistent with previous studies carried out during the COVID-19 pandemic [ 7 , 11 ], GPs proved their ability to improvise and use creative strategies. GPs in our study felt that they managed problems as they arose and tried to fight the pandemic to the best of their ability.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, GPs describe how they took charge of how care would be organised and implemented. Consistent with previous research [ 11 ], some GPs stated that during the COVID-19 pandemic they became the ‘new leaders’ within the healthcare organisation. Cognitive crafting can involve viewing work tasks as an important part of a larger whole, which also influences how employees approach their jobs [ 17 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…General practitioners (GPs) played a crucial role in the fight against the COVID-19 pandemic. However, they have experienced many barriers to fulfilling this role and many domains of quality of care have been affected [ 4 , 5 , 6 ]. For example, a scoping review revealed that healthcare access and utilization for both COVID and non-COVID-19 services decreased almost universally, across both higher- and lower-income countries [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, 95% of patients with RTIs are normally handled in general practice, comprising about 15% of all consultations [ 6 ]. After the lockdown in March 2020, follow-up of patients with COVID-19 outside hospitals was organized by the municipalities and varied between them, with nurse- and/or general practitioner-lead (GP) follow-up being the most common [ 7 , 8 ]. Routines for additional follow-up after the initial management varied but were often based on telephone calls or video consultations by the GP or dedicated primary health care personnel, regularly for a given time period, or until clinical recovery.…”
Section: Introductionmentioning
confidence: 99%